2013
DOI: 10.1002/hbm.22293
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of retinotopy constrained source estimation constrained by prior

Abstract: Studying how the timing and amplitude of visual evoked responses (VERs) vary between visual areas is important for understanding visual processing but is complicated by difficulties in reliably estimating VERs in individual visual areas using non-invasive brain measurements. Retinotopy constrained source estimation (RCSE) addresses this challenge by using multiple, retinotopically-mapped stimulus locations to simultaneously constrain estimates of VERs in visual areas V1, V2, and V3, taking advantage of the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 81 publications
2
33
1
Order By: Relevance
“…To the extent that this is the case, our peak latency values would be underestimated with respect to the real peak latency in area V1 alone. Using retinotopy constrained source estimation, Hagler (2014) reported a lengthening in V1 peak latency from 78 ms at close to 100% contrast to 100 ms at 15%, a relative delay that is slightly longer than we observed for most of our stimulus sizes. At the same time, the amount by which peak latency is delayed with decreasing contrast in our data - for example the relative delay of approximately 10 ms for 25% compared to 100% contrast gratings - is similar to that observed in the peak firing rate latencies of cats (Hu and Wang 2011) and in the V1 onset latencies measured using voltage sensitive dye imaging in monkeys (Sit et al 2009).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…To the extent that this is the case, our peak latency values would be underestimated with respect to the real peak latency in area V1 alone. Using retinotopy constrained source estimation, Hagler (2014) reported a lengthening in V1 peak latency from 78 ms at close to 100% contrast to 100 ms at 15%, a relative delay that is slightly longer than we observed for most of our stimulus sizes. At the same time, the amount by which peak latency is delayed with decreasing contrast in our data - for example the relative delay of approximately 10 ms for 25% compared to 100% contrast gratings - is similar to that observed in the peak firing rate latencies of cats (Hu and Wang 2011) and in the V1 onset latencies measured using voltage sensitive dye imaging in monkeys (Sit et al 2009).…”
Section: Discussioncontrasting
confidence: 53%
“…Studies based on scalp current density analysis (Foxe and Simpson 2002) and retinotopically constrained source modeling (Ales et al 2010; Hagler 2014; Hagler et al 2009) have provided evidence supporting the assumption that the C1 component is unlikely to reflect purely V1 activity for its entire duration, and may have mixed contributions from neighboring extrastriate areas such as V2 and V3 by the time it peaks. However, recent forward modeling of average scalp distributions generated purely from V2 and V3 revealed that these areas, when stimulated from visual field locations targeting the horizontally-oriented calcarine banks in V1, have scalp projections that significantly overlap those for area V1 but with reversed polarity (Ales et al 2013; see also Ales et al 2010; and Kelly et al 2013a for context).…”
Section: Discussionmentioning
confidence: 99%
“…A more trivial explanation, however, for the differences in measured response amplitudes is that the upper and lower field representations of V1 are located on the ventral and dorsal banks of the calcarine sulcus, respectively. Furthermore, V2 and V3 are each split into two, noncontig-Citation: Hagler, D. J., Jr. (2014). Visual field asymmetries in visual evoked responses.…”
Section: Introductionmentioning
confidence: 99%
“…Retinotopy constrained source estimation (RCSE) utilizing an individual's fMRI retinotopic-layout (fMRI-RL) has recently shown good success as an additional constraint to solve the close source problem [Ales et al, 2010;Cottereau et al, 2012;Hagler et al, 2009;Hagler and Dale, 2013;Hagler, 2014]. A RL is a collection of retinotopic maps organized anatomically into adjacent strips corresponding to visual areas, e.g.…”
Section: Introductionmentioning
confidence: 99%